INTEGRASI PENDIDIKAN DAN IMPLIKASINYA TERHADAP LEMBAGA PENDIDIKAN DI INDONESIA - Moh Kamilus Zaman (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
Integration has the meaning of merging or assimilating into one unified whole. In Indonesia, the concept of scientific integration has implications for the management of educational institutions. The release of SKB of three Ministers (Department of Education and Culture, Ministry of Home Affairs, and Ministry of Religion Affairs) which sets out the provision of curriculum in madrasah (Islamic school) which balancing between general curriculum and religious curriculum (70%: 30%) is a manifestation of this integration. SMA Nurul Jadid Probolinggo and MAN 3 Malang are able to apply an integrated learning. This is because those schools have facilitated dormitories for students with a series of Islamic-based activities outside learningtimes in kaffah. UIN Malang as the pioneer of establishment of ma’had or student’s dormitorieswhich used culture of education adapted from the culture of the university.UIN Malang and UIN Jakarta prefer to use approach of Imam Al-Ghazali which classify the sciences into fardlu ‘ain and fardlu kifayah by takwil method taken from social sciences. But UIN Jakarta used a paradigm of integration of dialogical science.